Habitat preference and niche partitioning in amphibians (Zoological Records and Reviews, 2023)
Niche partitioning -- the differential use of resources, space, or time among co-occurring species to reduce interspecificcompetition -- is a fundamental mechanism maintaining species diversity in ecological communities. Amphibianassemblages, where multiple species co-occur in shared wetland and forest habitats during the breeding season, providetractable systems for examining niche partitioning along multiple dimensions simultaneously. This study examines habitatpreference and niche partitioning in 32 co-occurring amphibian species across seasonal wetland, forest stream, androcky hill habitats of the Eastern Ghats in Andhra Pradesh and Telangana, India, using multivariate microhabitatcharacterisation, acoustic niche analysis, and temporal activity profiling at 24 sites surveyed over two monsoon seasons(2021-2022). Habitat partitioning is documented along five niche axes: breeding microhabitat (standing water vs. streamvs. terrestrial), calling site height, calling frequency (Hz), temporal calling activity pattern, and larval microhabitat. Nicheoverlap analysis confirms significant partitioning along all five axes, with acoustic niche partitioning (calling frequency andtiming) the strongest axis separating co-occurring species. Species pairs with high habitat overlap show significantlylower acoustic overlap than expected by chance, confirming acoustic character displacement. Microhabitat humidity,temperature, and vegetation structure are the strongest predictors of individual species microhabitat selection. Climatechange implications for acoustic niche disruption and interspecific competition are discussed.
Keywords: co-occurrence; Andhra Pradesh; microhabitat; Dicroglossidae; calling frequency; Eastern Ghats; acoustic niche; habitat preference; amphibians; niche partitioning